Impacto ambiental de los remanentes de supernova - Dubner, Gloria Mabel (2015)
The explosion of a supernovae (SN) represents the sudden injection of about 10^51 ergs of thermal and mechanical energy in a small region of space, causing the formation of powerful shock waves that propagate through the interstellar medium at speeds of several thousands of km/s. These waves sweep, compress and heat the interstellar material that they encounter, forming the supernova remnants. Their evolution over thousands of years change forever, irreversibly, not only the physical but also the chemical properties of a vast region of space that can span hundreds of parsecs. This contribution briefly analyzes the impact of these explosions, discussing the relevance of some phenomena usually associated with SNe and their remnants in the light of recent theoreticaland observational results.